2014
DOI: 10.1016/j.quascirev.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Glacial retreat in the Amundsen Sea sector, West Antarctica – first cosmogenic evidence from central Pine Island Bay and the Kohler Range

Abstract: a b s t r a c tThe Amundsen Sea Embayment of West Antarctica hosts one of the most rapidly changing sectors of the West Antarctic Ice Sheet. With the fastest-flowing ice streams in Antarctica, the region around Pine Island Bay is characterized by rapid ice-sheet thinning and grounding-line retreat. Published surfaceexposure data are limited to a few isolated nunataks making it difficult to assess the long-term deglacial history of the area. To address this, we correlate existing records of lateral ice-stream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
(76 reference statements)
1
20
0
Order By: Relevance
“…It has also been suggested that some of these basins hosted, at least temporarily, subglacial lakes during the last glacial period [ Nitsche et al ., ; Witus et al ., ]. Surface exposure ages of glacially transported rocks have shown that the LGM surface of the WAIS lay at least ~140 m and 190 m higher than today to the north and to the east of the modern PIG grounding‐line position, respectively [ Johnson et al ., , ], while in the hinterland of the Crosson and Dotson ice shelves the LGM ice sheet was ~300 to 330 m thicker than today [ Johnson et al ., ; Lindow et al ., ].…”
Section: Glaciological Changes In the Asementioning
confidence: 99%
See 3 more Smart Citations
“…It has also been suggested that some of these basins hosted, at least temporarily, subglacial lakes during the last glacial period [ Nitsche et al ., ; Witus et al ., ]. Surface exposure ages of glacially transported rocks have shown that the LGM surface of the WAIS lay at least ~140 m and 190 m higher than today to the north and to the east of the modern PIG grounding‐line position, respectively [ Johnson et al ., , ], while in the hinterland of the Crosson and Dotson ice shelves the LGM ice sheet was ~300 to 330 m thicker than today [ Johnson et al ., ; Lindow et al ., ].…”
Section: Glaciological Changes In the Asementioning
confidence: 99%
“…Estimates of the time that surface rocks around the ASE have been exposed (see Dunai [] for details of the types of technique used) indicate that significant post‐LGM ice sheet thinning occurred in the hinterland of the Dotson Ice Shelf between 12.6 and 8.6 ka [ Lindow et al ., ] and in the hinterland of the Crosson Ice Shelf between 14.5 and 11.7 ka [ Johnson et al ., ], which is consistent with the reconstructions from the marine sediment cores. However, the data also revealed rapid WAIS thinning in the Pine Island Bay region at ~8 ka, i.e., >3000 years later than the deglaciation of the inner shelf [ Johnson et al ., ].…”
Section: Glaciological Changes In the Asementioning
confidence: 99%
See 2 more Smart Citations
“…Cosmogenic exposure-age dating, which relies on the measurement of rare nuclides produced in rock surfaces and sediments by cosmic ray bombardment, is now widely used to date both late Pleistocene and Holocene deglaciation ages as well as to quantify subglacial erosion rates via the nuclide concentration in glacially transported boulders and in bedrock exposed during retreat (Balco, 2011). Advances in the use of cosmogenic nuclide isotopes (Miller et al, 2002;Briner et al, 2006;Briner and Kaufman, 2008;Menounos et al, 2009;Balco, 2011;Fastook and Hughes, 2013;Granger et al, 2013;Champagnac et al, 2014;Cofaigh et al, 2014;Hormes et al, 2013;Refsnider et al, 2013;Hodgson et al, 2014;Larter et al, 2014;Lindow et al, 2014;Rother et al, 2014;Winsor et al, 2014) have helped resolve a number of longstanding chronological and process debates in geomorphology, including: topographic relief development (e.g., Tremblay et al, 2014) and the ability of cold-based ice sheets to preserve pre-glacial landscape features (e.g. Stroeven et al, 2002;Briner et al, 2006); complex Holocene glacial exposureburial histories (e.g.…”
Section: Observations Of Glacial Erosion and Sediment Productionmentioning
confidence: 99%